GRAMMATICAL COHESION IN STUDENTS’ UNDERGRADUATE THESIS - Ari Prasetyaningrum; Maman Asrobi; Siti Ayu Surayya; Zahratul Fikni (Universitas Muhammadiyah Metro, 2022)
The goals of this study were to find out the most dominant types of grammatical cohesion used in undergraduate thesis belonged students of study program of English language education at Hamzanwadi university by M.A.K Halliday’s theory. This study was classified into descriptive qualitative research with discourse approach. The author used documentation in the form of students’ undergraduate thesis for collecting the data. There were two kinds of data taken, namely primary and secondary data. The primary data referred to the thesis written by the learners of the eight semesters as their partial fulfilment task before having bachelor degree. The secondary data was data that complete the main data. The author showed the data in line with Creswell and Poth theory in which the author related the theory by examining the grammatical of the thesis. The research finding revealed the most dominant type of grammatical cohesion was reference which appear 6149 times or 65, 29 % then conjunction which was found 3107 times or 32, 99 %. Meanwhile, the least dominant types of grammatical cohesion were substitution which appeared 145 times (1, 53%) and ellipsis which appeared 16 times (0, 16%).